Global Capitalism and the Lahures : A Study of Modernity in Anagarik, a Film Directed by Rambabu Gurung - Thapa, Bal Bahadur (SCHOLARS: Journal of Arts & Humanities, 2021)
The Nepali men, also known as the Gorkhas, who joined the colonial British army during and after the Anglo-Nepal War (1814-16), are considered the first foreign economic migrants. These Nepali men, who used to be popularly known as Lahures in their villages, proved to be one of the major harbingers of modernity in Nepal. Since the 1990s, other types of Nepali economic migrants, along with these Lahures, have shaped the Nepali modernity. Against this backdrop, this paper analyzes the Lahure culture in Rambabu Gurung’s debut film Anagarik [The Unbecoming Citizen] in the light of discourses of modernity. Locating the Lahure culture in the national as well as international historical contexts, this study fleshes out a few major findings. Firstly, the Lahure culture is a significant factor, which has heralded and sustained modernity in Nepal. Secondly, it connected Nepal to the world outside even during the Rana rule. Thirdly, the recent trend of Nepalis migrating abroad for employment is nothing but the variation as well as continuation of the same Lahure culture. Fourthly, the Lahure culture is symptomatic of Nepal’s status as a peripheral country in the capitalist world order. This paper is expected to contribute to the ongoing debates surrounding modernity, international migration and Nepal's position in the global capitalist order.